PROSPECTS FOR ADVANCING DESCRIPTIVE GEOMETRY EDUCATION IN THE METAVERSE ENVIRONMENT - Yusubjonov Jonibek Farkhod ugli (Modern American Journals, 2025)
The Metaverse, as an immersive digital environment, presents new opportunities for enhancing education in disciplines requiring spatial reasoning and visualization, such as Descriptive Geometry. By leveraging virtual reality (VR), augmented reality (AR), and interactive 3D platforms, educators can create highly engaging, interactive, and adaptive learning experiences. This study explores strategies for developing Descriptive Geometry education in the Metaverse, focusing on pedagogical approaches, platform design, and student engagement. Using the IMRaD framework, the research combines literature review, experimental implementations, and analysis of learner performance in virtual environments. Results indicate that Metaverse-based education significantly improves spatial understanding, motivation, and collaborative problem-solving skills, while enabling individualized learning paths. The discussion addresses technical, pedagogical, and accessibility challenges. The conclusion emphasizes the transformative potential of the Metaverse in modernizing Descriptive Geometry education and preparing students for digitally-mediated professional environments.
Keywords: Descriptive Geometry, Metaverse, Virtual Reality, Augmented Reality, Interactive Learning, STEM Education, Digital Pedagogy, 3D Visualization.